Westphalen's diol diacetate: 19(10→5)-abeo-5β-cholest-9-ene-3β,6β-diyl diacetate - Ramírez Hernández, Johana; Sandoval Ramírez, Jesús; Meza Reyes, Socorro; Vega Báez, José Luis; Bernès, Sylvain (Wiley-Blackwell, 2012)
The structure of the title steroid [alternative name: 3,6-diacetoxy-5-methyl-19-norcholest-9(10)-ene], C31H50O4, confirms the generally accepted mechanism for the rearrangement of a cholestan-5-ol derivative reported a century ago by Westphalen. The methyl group at position 10 of the starting material migrates to position 5 in the steroidal nucleus, while a 9 bond is formed, as indicated by the C C bond length of 1.347 (4) A